Análises físico-químicas e virucidas da fermentação com cobertura e sem amontoamento da cama de aves - Flavio Marcio Santos Resende (2010)
Broiler litter fermentation has been recommended for reuse of poultry bedding, ensuing the maturation of broiler litter, in order to reduce disease risk for consecutive flocks. A pilot experiment was set up for evaluating controlled fermentation conditions and their effects on the infectivity of Newcastle disease (NDV) or infectious bursal disease (IBDV) viruses. Litter was collected from a SPF chicken flock, homogenized and distributed into experimental groups. Groups were divided into two subgroups, according to fermentation with plastic covering or not, and infected with 108,21 NDV La Sota embryo infective doses (EID50)/kg litter or 102,69 IBDV Lukert EID50/kg litter, in chronologically separated experiments. Samples were collected at days zero, four, eight and 11 of fermentation for the measurement of NH3 and for the evaluation of virus infectivity. Litter temperature was measured daily. A field study was similarly performed, with two groups (covered or not) and six repetitions of IBDV vaccinated broilers sampled at days zero and 12 of fermentation for the evaluation of virus infectivity. For the evaluation of virus infectivity, were selected 10-day incubating SPF chicken embryos and embryonic inoculations were performed with litter extracts, after clarification and treatment with antibiotic solution. Litter temperature was measured daily. Humidity, NH3 and pH were measured by sampled at days zero, four, eight and 12 of fermentation. NDV was completely inactivated in litters subject to >8 or more days of fermentation, covered or not. IBDV was not inactivated in either fermentation litters subject to 12 days of fermentation. NDV inactivation appeared to be mediated by NH3 or other chemical effect, but no temperature, which did not elevate to inactivating levels. Humidity, NH3, and pH were significantly higher in covered fermentation. It was concluded that 12-day fermentation may be performed for inactivating NDV and recycling broiler litters. However, the recycled product may not be safe regarding IBDV.